A cost-benefit analysis of small biofuel projects in Fiji: Lessons and implications. (15th March 2022) - Lal, Richard; Kumar, Sunil; Naidu, Suwastika
Abstract: Like other developing countries, rural electrification is a longstanding priority for Pacific Island Countries (PICs). Scores of renewable resources are being mobilised to achieve rural electrification and green energy targets, given the growing concerns with fossil fuels. This transition is often costly for PICs, or broadly, poor developing countries. By adopting a nomothetic approach, this study examines the mobilisation of resources for rural electrification projects in Fiji under their National Biofuel Implementation Program. We find that these projects have only been successful in minimal circumstances, and the projects in operation are under significant stress due to mismanagement or lack of resources. A key reason for failure has been insufficient capacity and poor project design—the study analyses the causes and attempts to fill the knowledge gap through a cost-benefit analysis. We consider the first three sites where the relevant data was gathered through field surveys using a semi-structured approach. Only one of the three project sites is successful due to greater community involvement and participation through functional traditional governance systems. Key findings also indicate potential lessons for policymaking and relevant implementation processes that would benefit PICs and other small developing countries looking at similar projects. Highlights: The biofuel program under Fiji's rural electrification policy is investigated. A case study of the Rotuma, Koro and Cicia implementation sites is conducted. Cost-benefit analysis results are favourable only for Rotuma. Fiji government needs to revisit their project design and approach.